Relationship of Knowledge with PGK Patient compliance Underwent Hemodialysis in the Hemodialysis Unit of the Hospital Santa Elisabeth Medan - Nagoklan Simbolon; Pomarida Simbolon (Science Midwifery, 2019)
The 2015 IRR data showed that hemodialysis service facilities in Indonesia were classified into two institutions, namely 92.1% hospital installations and 7.9% clinics. The cost burden incurred by BPJS for the treatment of kidney failure was the second largest sequence after heart disease. Costs incurred in 2014 amounted to 1.6 trillion rupiahs, increased to 2.7 trillion rupiahs in 2015 and decreased slightly in 2016 to 2.5 trillion rupiahs. Success in maintaining kidney health and restoring kidney function to CKD patients requires knowledge as a guide in implementing healthy living behavior for people who are still healthy kidney and undergoing dialysis therapy for CKD patients. This study aims to determine the relationship between knowledge of hemodialysis and treatment of carrying out hemodialysis at the Hospital Unit of Santa Elisabeth Medan in 2018. This type of survey research was explanatory. The research sample was 30 people, using a total sample with consecutive sampling technique. Methods of data analysis used univariate and bivariate with p value 0.001, meaning that there was a relationship between knowledge of hemodialysis and adherence to hemodialysis in the Hemodialysis Unit of the Hospital Elisabeth of Medan. Further analysis obtained OR value of 22,667 with 95% CI (3,140 -163,629), meaning that CKD patients undergoing hemodialysis who were obeyed 22,667 times were likely to have good knowledge about hemodialysis compared with CKD patients undergoing non-adherent hemodialysis. Students are expected to provide health education,